Reclaiming Public Culture as a Common Terrain of Action in the Public Interest: A Dialogue with Raluca Iacob - PANCU, Livia (Studia Universitatis Babeș-Bolyai Dramatica, 2022)
Raluca Iacob is a cultural manager, a cultural policy analyst and an independent researcher, president of MetruCub – resources for culture Association. Among others, she coordinated the formulation of the cultural strategy of the city of Timișoara for 2014-2024 (together with Vera Marin and commissioned by the Municipality of Timișoara) and, as councillor to the minister of culture in 2016, the design of the national strategy for culture and heritage. Other relevant collaborations with: the Center for Consultancy for European Cultural Programmes, the Romanian Academic Society, the Romanian Federation of Community Foundations and the European Network of Cultural Centres. Currently she is interested in practices and policies of culture in education, in alternative models of cultural governance and in cultural networks.